Complete genome sequence of Halomonas sp. R5-57 - Williamson, Adele Kim; De Santi, Concetta; Altermark, Bjørn; Karlsen, Christian; Hjerde, Erik (Standards in Genomic Sciences, 2016)
The marine Arctic isolate Halomonas sp. R5-57 was sequenced as part of a bioprospecting project which aims to discover novel enzymes and organisms from low-temperature environments, with potential uses in biotechnological applications. Phenotypically, Halomonas sp. R5-57 exhibits high salt tolerance over a wide range of temperatures and has extra-cellular hydrolytic activities with several substrates, indicating it secretes enzymes which may function in high salinity conditions. Genome sequencing identified the genes involved in the biosynthesis of the osmoprotectant ectoine, which has applications in food processing and pharmacy, as well as those involved in production of polyhydroxyalkanoates, which can serve as precursors to bioplastics. The percentage identity of these biosynthetic genes from Halomonas sp. R5-57 and current production strains varies between 99 % for some to 69 % for others, thus it is plausible that R5-57 may have a different production capacity to currently used strains, or that in the case of PHAs, the properties of the final product may vary. Here we present the finished genome sequence (LN813019) of Halomonas sp. R5-57 which will facilitate exploitation of this bacterium; either as a whole-cell production host, or by recombinant expression of its individual enzymes.